STUDI KESESUAIAN TATA RUANG PASAR TRADISIONAL SITEBA KECAMATAN NANGGALO KOTA PADANG - Sulvianti, Dina Sulvianti; Bakaruddin, Bakaruddin; Juita, Erna (STKIP PGRI Sumbar, 2013)
This study aims to determine the suitability of spatial traditional market of Siteba District of Nanggalo PadangCity.This research is descriptive. The population in this study are existing traders in traditional market of Siteba District of Nanggalo PadangCity consisting of merchants and merchant stalls stone table plots totaling 209 merchants. Samples were taken with proportional randomsampling techniques, with the proportion of 50%, thus totaling 104 samples resoponden merchant.Study found that: 1) Location of traditional market of Siteba District of Nanggalo PadangCity which means the location is quite good enough to qualify the market in accordance with the criteria for the location of a market, 2) means of traditional market of Siteba District of Nanggalo PadangCity category quite well, meaning the market means not qualify a traditional market, 3) infrastructure traditional market of Siteba District of Nanggalo PadangCity category quite well, meaning the market infrastructure still needs to be added as yet according to market criteria traidisonal and 4) security traditional market of Siteba District of Nanggalo PadangCity categorized as good, meaningful security market has been qualified for a market.